2017
DOI: 10.3390/v9020026
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Herpes Simplex Virus Type 1 Infection in Rhesus Macaques and the Associated Pathological Features

Abstract: As one of the major pathogens for human herpetic diseases, herpes simplex virus type 1 (HSV1) causes herpes labialis, genital herpes and herpetic encephalitis. Our aim here was to investigate the infectious process of HSV1 in rhesus macaques and the pathological features induced during this infection. Clinical symptoms that manifested in the rhesus macaque during HSV1 infection included vesicular lesions and their pathological features. Viral distribution in the nervous tissues and associated pathologic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…We also noted the presence of marked desquamative monolymphocytic enterocolitis in the small intestine of the primates of our study, which was also reported in the intestine of Alouatta caraya by Barnes et al, in the intestine and stomach of C. jacchus and C. penicillata by Casagrande et al and A. azarae by Kreutzer et al [11,20,35]. Fan et al, however, stated that in the structural damage was observed in the brain and other organs of the M. mullata inoculated with HSV-1 [15]. These authors suggested that HSV-1 infection was capable of inducing vesicular lesions in the oral skin or mucosa of mediating viral replication at least in nervous tissues through an unknown mechanism without pathological damage.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We also noted the presence of marked desquamative monolymphocytic enterocolitis in the small intestine of the primates of our study, which was also reported in the intestine of Alouatta caraya by Barnes et al, in the intestine and stomach of C. jacchus and C. penicillata by Casagrande et al and A. azarae by Kreutzer et al [11,20,35]. Fan et al, however, stated that in the structural damage was observed in the brain and other organs of the M. mullata inoculated with HSV-1 [15]. These authors suggested that HSV-1 infection was capable of inducing vesicular lesions in the oral skin or mucosa of mediating viral replication at least in nervous tissues through an unknown mechanism without pathological damage.…”
Section: Discussionsupporting
confidence: 78%
“…The herpesvirus was isolated in Vero cells in brain samples from the marmosets and the cytopathic effects observed were, cells decrease with rounding, refringence and detachment in 2 days, aspects also observed in other studies of HSV-1 in C. jacchus, Hylobates a. agilus and in M. mulatta [13,15,38]. To the transmission electron microscope, we visualized by means of negative staining, typical particles of herpesvirus, isometric, exhibits enveloped and non-enveloped particles, showing nucleocapsids stain penetrated and non-strain penetrated, measuring 120-200 nm of diameter.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This is due at least in part to the absence of a relevant animal model for studying oral HSV-1 co-infection in the context of HIV infection. Only one recent study described oral HSV-1 infection in rhesus macaques (Fan et al, 2017 ), and this was in the absence of SIV. The majority of NHP studies of HSV-1 infection have used new world NHPs, with highly pathogenic outcomes (Kaufman, 1963 ; Katzin et al, 1967 ; Varnell et al, 1987 , 1995 ; Rootman et al, 1990 ; Hunter et al, 1999 ; Deisboeck et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these models are inadequate for studying HSV-1 immunology as it relates to humans or HSV-1/SIV co-infection. Only one recent report described oral HSV-1 infection in rhesus macaques after lip scarification (Fan et al, 2017 ), and we recently described genital HSV-1 infection in SHIV-infected macaques (Aravantinou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%